1997
DOI: 10.1063/1.365406
|View full text |Cite
|
Sign up to set email alerts
|

A diffusional model for the oxidation behavior of Si1−xGex alloys

Abstract: We have developed a kinetic model to describe the oxidation behavior of Si1−xGex alloys during Ge segregation, which compares the Deal–Grove flux of oxidant diffusing through the oxide to the maximum flux of Si diffusing through the Ge-rich layer. This is motivated by thermal oxidation experiments on Si1−xGex alloys (x<0.17) using a fluorine-containing ambient (O2 and 200 ppm of NF3). The fluorine is known to modify point defect generation during oxidation of pure Si toward vacancy production, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…First, there is an enhancement of the SiGe dryoxidation rate over that of pure Si, which was previously observed only for thermal-wet oxidation. Recently, fluorine-assisted dry oxidation 6 and atomic-oxygen oxidation 12 studies reported a similar enhancement. It has been suggested 9 that because The behavior of Ge atoms during dry oxidation of Si 0.8 Ge 0.2 films at 300°C under 10 mbar of oxygen induced by vacuum-ultraviolet (VUV) illumination from an array of Xe 2 * excimer lamps ( ϭ 172 nm) has been studied.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…First, there is an enhancement of the SiGe dryoxidation rate over that of pure Si, which was previously observed only for thermal-wet oxidation. Recently, fluorine-assisted dry oxidation 6 and atomic-oxygen oxidation 12 studies reported a similar enhancement. It has been suggested 9 that because The behavior of Ge atoms during dry oxidation of Si 0.8 Ge 0.2 films at 300°C under 10 mbar of oxygen induced by vacuum-ultraviolet (VUV) illumination from an array of Xe 2 * excimer lamps ( ϭ 172 nm) has been studied.…”
Section: Introductionsupporting
confidence: 56%
“…23,24 However, this effect can only explain the enhancement of the semiconductor-oxidation rate. The trapping of Ge during SiGe-oxidation experiments has been explained by a competition between the oxidant flux from the surface and the Si atoms flux from the substrate: 5,6,[9][10][11][12] as long as the flux of Si atoms is equal or greater than the oxidant flux, the grown oxide layer will contain only SiO 2 , while all Ge atoms will be segregated from this newly formed oxide layer. Because the growth rates in our VUV-assisted oxidation experiment and ozone-assisted oxidation are very similar one can infer that the oxidant fluxes should also be very similar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Oxidation of SiGe layers leads to some Ge segregation, to an increase of the SiO 2 /SiGe interface roughness, and to the presence of numerous interface electrical defects. 4,5 Typically, an interfacial layer is formed due to uncontrolled chemical reaction at the interface with the substrate. The common procedure to reduce interfacial trap density in the developed layer is post deposition annealing (PDA), 6,7 which has a wide range of effects on the HfO 2 /Si based interface.…”
mentioning
confidence: 99%